2019
DOI: 10.3389/fpls.2019.00116
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Selenate Treatment Using a Combination of Seed Priming and Foliar Spray Alleviates Salinity Stress in Rice

Abstract: Soil salinity is one of the important abiotic stress factors that affect rice productivity and quality. Research with several dicotyledonous plants indicated that the detrimental effects associated with salinity stress can (partly) be overcome by the external application of antioxidative substances. For instance, sodium selenate (Na2SeO4) significantly improved the growth and productivity of several crops under various abiotic stress conditions. At present there is no report describing the impact of Na2SeO4 on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 85 publications
3
64
0
Order By: Relevance
“…Moreover, enhanced growth and nutritional qualities of spinach (Spinacia oleracea L.), ryegrass (Lolium perenne L.), wheat (Triticum aestivum L.), and mung bean (Vigna radiate L.) have also been reported by exogenously applied Se under stressed and non-stressed conditions [22,106,142,146]. Further, a lower Na + concentration and higher K + /Na + ratio was observed in selenite-treated plants as compared to untreated plants [27]. Se might have decreased the accretion of Na + ions which led to an increased K + /Na + ratio in comparison to the untreated control plants of dill (Anethum graveolens) and garlic (Allium sativum L.) [129,147].…”
Section: Se-mediated Improvement In Physiological Attributesmentioning
confidence: 96%
See 4 more Smart Citations
“…Moreover, enhanced growth and nutritional qualities of spinach (Spinacia oleracea L.), ryegrass (Lolium perenne L.), wheat (Triticum aestivum L.), and mung bean (Vigna radiate L.) have also been reported by exogenously applied Se under stressed and non-stressed conditions [22,106,142,146]. Further, a lower Na + concentration and higher K + /Na + ratio was observed in selenite-treated plants as compared to untreated plants [27]. Se might have decreased the accretion of Na + ions which led to an increased K + /Na + ratio in comparison to the untreated control plants of dill (Anethum graveolens) and garlic (Allium sativum L.) [129,147].…”
Section: Se-mediated Improvement In Physiological Attributesmentioning
confidence: 96%
“…Some studies have shown that Se is an essential element for human and animal, which plays some beneficial roles in higher plants. Selenium application caused an increasing growth in rice (Oryza sativa L.) [27] and wheat (Triticum aestivum L.) [28], under both stressed and non-stressed conditions. Se has been demonstrated to regulate plant growth by strengthening the stress tolerance mechanisms such as antioxidant and secondary metabolite metabolism [29].…”
Section: Of 27mentioning
confidence: 99%
See 3 more Smart Citations